A novel axial modification and simulation analysis of involute spur gear - Wang, Ningning (Strojniški vestnik, 2017)
The transmission of spur gear mechanism may generate uneven load distribution because of machining error, assembly error, elastic deformation, and other factors, resulting in serious damage to the bearing capacity and service life of gears. To improve the contact condition of gear pairs and enhance the meshing performance and bearing capacity, this study proposed a novel axial modification method based on a composite modification curve with indefinite parameters and an evaluation method to evaluate modification effects. In addition to the surface equation of modified tooth was derived according to the composite modification curve, and the finite element model was built for gear pair. After conducting simulation analysis for the meshing process, the location and the shape of contact area as well as the other results can be acquired. In addition, the modification parameters can be optimized by performing orthogonal experiments for modified gear pairs; thus, the ideal modification effect is obtained at a specific operating condition. Moreover, comparison analysis was performed, and the results show that the phenomenon of uneven load distribution is dramatically improved when the gear pair was modified with optimized parameters, and the bearing capacity of the gear pair was increased. Finally, using the optimized parameters to trial-produce gears and conducting running-in tests, the effectiveness and the practicability of the method proposed in this study were verified.
Keywords: aksialna modifikacija; kontaktne površine; neenakomerna porazdelitev obremenitev; optimizacija; simulacijske analize; učinek modifikacije